2008
DOI: 10.1002/pon.1358
|View full text |Cite
|
Sign up to set email alerts
|

Social‐cognitive aspects of underserved Latinas preparing to undergo genetic cancer risk assessment for hereditary breast and ovarian cancer

Abstract: Objectives: As Latinos are a growing ethnic group in the United States, it is important to understand the socio-cultural factors that may be associated with cancer screening and prevention in this population. The socio-cultural factors that may affect preparedness to undergo genetic cancer risk assessment (GCRA) deserve particular attention. The pre-GCRA period can provide insight into variables that may influence how medically underserved Latinas, with limited health resources and access, understand hereditar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 62 publications
2
41
1
Order By: Relevance
“…Furthermore, ethnic identity has been associated with increased use of social support in Asian Americans, which in turn has been associated with decreased perceptions of race-related stress [13]. Additionally, Latina women with lower levels of acculturation (i.e., preserving ethnic identity) report higher levels of coping self-efficacy and perceived support in coping with genetic cancer screening results [14]. Taking together this work in view of Anderson's [6] theoretical model proposed previously, it is plausible to propose that coping self-efficacy and social support mediate the relationship between ethnic identity and psychological stress.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, ethnic identity has been associated with increased use of social support in Asian Americans, which in turn has been associated with decreased perceptions of race-related stress [13]. Additionally, Latina women with lower levels of acculturation (i.e., preserving ethnic identity) report higher levels of coping self-efficacy and perceived support in coping with genetic cancer screening results [14]. Taking together this work in view of Anderson's [6] theoretical model proposed previously, it is plausible to propose that coping self-efficacy and social support mediate the relationship between ethnic identity and psychological stress.…”
Section: Introductionmentioning
confidence: 95%
“…Our understanding about attitudes towards genetic testing for predisposition genes for cancers in non-Caucasian populations are largely based on studies done on minority populations, particularly amongst the African-American and Hispanic populations in the United States [3,[6][7][8][9][10]. In these populations, disparities in uptake of cancer genetic services have been described and may be attributable to differences in exposure to genetic information and referral by health care providers, but are not explained by differences in risk factors for carrying a BRCA1/2 mutation, socioeconomic factors, risk perception, or attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…However, some participants with fatalistic thoughts may not have expressed their concerns about inherited risk of cancer. In a study of women with a personal or family history of breast or ovarian cancer, Lagos et al [40] revealed that fatalism was less prevalent in women who had high levels of self-efficacy. In the present study, participants who mentioned coping (risk-reducing) behavior may have had higher levels of self-efficacy compared with other patients.…”
Section: Discussionmentioning
confidence: 98%